Sinonasal papillomas in Quito, Ecuador - Pacheco-Ojeda, L.; A., Ayala Ochoa; C., Ríos (International Surgery Journal, 2018)
Background: Sinonasal inverted papilloma is an unusual tumor of the nasal cavity and paranasal sinuses with potential for malignant transformation. The objective was to review the experience mostly using a similar open surgical approach. Methods: Twenty-eight patients were included. Mean age was 54, 57% of male gender. five patients were previously operated elsewhere, twenty-five had unilateral complete nasal obstruction and mean duration of symptoms was 8months. A computed tomography was performed in all patients. The tumor was located within the nasal cavity in 9 cases, limited to the ethmoid sinus complex in one, extended to the maxillary sinus in 16 and to the nasopharynx or palate in one, each. Mean size was 5.2cm. Twenty-seven cases were benign and one was a transitional carcinoma originated in an inverted papilloma. Surgical resection of the tumor was performed through a Denker’s approach in all the benign cases except a lateral rhinotomy in one recurrent lesion of limited ethmoid involvement. A partial maxillectomy was performed in the patient with malignancy. Minor postoperative complications occurred in 3 patients which was nasal bleeding, a cellulitis of the cheek with exophtalmus and an oro-antral fistula. Results: After a mean follow-up of 33.6months, recurrent benign tumors were easily resected through the same approach in 5 patients. All patients have currently no evidence of disease. Conclusions: Denker’s approach was a very useful, rapid and safe surgical approach for treatment of middle size or extended sinonasal inverted papillomas and remains an alternative to current endoscopic resection.